Analysis of Results of Emergency Training Proficiency For High School Physical Education Teacher in East Java - Tulloh, Bima Revolusi Samudra; Rosidi, Sakban; Lani, Ahmad (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
Even though you have tried to prevent it, accidents in learning sports can still happen. Physical education teachers are certainly required to be responsive and capable of handling it. What are the emergency training needs faced by high school physical education teachers and analysis of the results of emergency training for high school physical education teachers. The purpose of this study was to determine the variety of emergency events and the level of need for first aid training for a high school physical education, sports and health teacher in East Java. In this study using models and theoretical concepts with an andragogical perspective using the Training Need Assessment as well as the theory of needs and gaps. This correlation descriptive study examines the analysis of the results of emergency training for high school physical education teachers. Data were collected by means of an online questionnaire. The results of the study concluded: 1) Various sports emergency events, namely leg muscle cramps, blisters on the skin, fainting due to heat, hand muscle cramps, stomach muscle cramps, bruises on the skin, tears in the skin, respiratory failure, drowning in swimming pools, sprains, nosebleeds, and bone dislocations. 2) Ten sports emergency incidents which are needs for sports emergency training, one unfulfilled need/real needs and nine felt needs. 3). There is a significant relationship between events and proficiency levels and between proficiency levels and the readiness of high school physical education teachers.